Westerweel Group Non-Conformist Resistance Against Nazi-Germany - A Joint Rescue Effort of Dutch Idealists and Dutch-German Zionists - Schippers, Hans 1946- (New Perspectives on Modern Jewish History Ser., 2019)
The peer-reviewed series seeks to provide an international platform for new approaches to the study of modern Jewish history. Covering the period from the Enlightenment to the 21st century, the series focuses on cutting-edge work in social, cultural, economic, and political history. It seeks to explore new avenues in the understanding of modern Jewries in their historical contexts, encouraging a multi-layered exploration of topics which transcend the analytical boundaries of ethnicity, nation, and religion. The series embraces monographs and challenging research-oriented anthologies dedicated to a deeper understanding of essential themes in the main fields of Jewish studies, such as Jewish thought, migration, biography, Israel and the Middle East, Holocaust studies, the history of memory, and identity.